Calibrating capital buffers for other systemically important institutions (O-SIIs) in Germany - Utilising the equal expected impact approach - Sebastian Geiger; Marcel Heires; Ulrich Krüger; Johannes Ludwig; Ursula Vogel (Deutsche Bundesbank, 2022)
A new approach, derived from the equal expected impact (EEI) approach, was used for the calibration of the buffers for other systemically important institutions (O-SIIs) in Germany in 2020. This technical paper presents a detailed background to the EEI approach as used for the updated calibration. First, we explain the economic intuition and the theoretical background of the EEI approach. We then proceed to implement it for the German banking system and present the result of its operationalisation. Finally, we discuss limitations of the EEI approach and specify issues to be addressed in future calibration approaches for O-SII buffers.
Keywords: E52; F33; G21; 330; O-SII buffer; too-big-to-fail; capital buffer calibration; equal expected impact